Handbook on the European Union and Brexit - Fossum, John E.; Lord, Christopher (Edward Elgar Publishing, 2023)
"Brexit has irrevocably transformed British politics, yet its effects are not confined to relations between the UK and the EU. Venturing beyond the already vast literature on Brexit, this dynamic Handbook explores the implications of the UK's withdrawal from the EU for the EU itself, single countries within and beyond Europe, and the international system, as well as different social groups, generations, and territories within the UK. John Erik Fossum and Christopher Lord bring together 29 expert contributions on the multiple actors and processes which have shaped Brexit. State-of-the-art chapters cover the various factors which led to the success of the 'Leave' campaign, the role of EU institutions in Brexit, the implications for other member states and players in the international system, and questions of political legitimacy posed by the UK's departure from the EU. The Handbook concludes with a discussion of the alternative relationships and opportunities available to the UK in the post-Brexit era. Advancing multiple specialised perspectives on and approaches to Brexit, this comprehensive Handbook will be an invaluable resource for students and scholars of British and EU politics. Its overview of recent developments in the EU will allow researchers and research institutes to develop their own work on Brexit"--